Professional Variables and Staff Readiness to Utilise Internet-Based Channels for Research Communication in an Era of Covid-19 - Owan, Valentine, Joseph; Akah, Levi, Udochukwu; Ogbeche, Mary, Mark (My University, 2021)
This study assessed the professional variables of academic staff in African varsities and their readiness to Utilise Internet-Based Channels for Research Communication in an era of Covid-19. Drawing from Maslow’s hierarchy of needs theory, the study was guided by four null hypotheses. The quantitative research method based on the virtual cross-sectional survey design was adopted. A total of 8,591 academics in African
Keywords: Africa; Covid-19; Internet tools; Professional variables; Research; Staff readiness